Răspunsuri

Cel mai inteligent răspuns!
2014-03-21T21:07:00+02:00
1,(6) inseamna 1 intreg si 6/9 adica (1*6+9)/9=15/9=5/3
0,(3)=3/9=1/3
a+b=1,(6)⇔a+b=5/3⇒a=5/3-b
a-b=0,(3)⇒5/3-b-b=1/3⇒-2b=1/3-5/3⇒-2b=-4/3⇒b=4/3*1/2⇒b=4/6=2/3
                                                                                    ⇒a=5/3-2/3=3/3=1
2 5 2
2014-03-21T21:23:45+02:00
1,(6) = 5/3 si 0,(3) = 1/3

x + y = 5/3
x  - y = 1/3
Adunam ecuatiile si scapam de y
=>  2x = 6/3    => x = 3/3 = 1
x + y = 5/3    dar stim ca x = 3/3
3/3 + y = 5/3     =>  y = 5/3 - 3/3 = 2/3 = 0,(6)

=> x =